Teachers' perception on the smart school training programme : its applicability to classroom management - Poniman, Bin Bejok. (1999)
This research aims to study teachers’ perceptions toward Smart School training with respect to classroom management to classroom management in six Smart Schools in Sarawak. The study is restricted to the computer aspect of the training and will not in any way describe other aspects of the Smart School training programme.